Decreased precipitation frequency altered abundance, but not community structure, of soil nematodes in degraded grasslands. (November 2021) - Chen, Junda; Yao, Yuan; Wang, Gui; Zhong, Xiaoyue; Yang, Tianxue; Sun, Wei
Highlights: Decreased precipitation frequency suppressed nematode abundance, especially for bacterivores. Nematode community structure was not affected by the altered precipitation frequency. Responses of nematodes to the altered precipitation were divergent in different degraded grasslands. Abstract: Rainfall patterns in arid and semi-arid regions are characterized by a reduction in rainfall frequency. However, under this novel climatic condition, potential changes in soil nematode community among different degraded grasslands remain unclear. We conducted a mesocosm experiment to test the effects of lower precipitation frequency (decreased by 50% from the long-term mean) on nematodes in the lightly degraded (LDG), moderately degraded (MDG) and severely degraded grasslands (SDG). The decreased precipitation frequency treatment significantly reduced the total abundance of nematodes by reducing soil moisture and enhancing moisture variability. Compared with other trophic groups of nematode, bacterivores were more sensitive to the altered precipitation and were significantly suppressed by higher soil moisture variation caused by lower precipitation frequency in the degraded grasslands. The decreased precipitation frequency treatment promoted plant belowground biomass through increasing soil moisture variation, which promoted plant parasites in LDG. However, in MDG and SDG, plant parasites were mainly suppressed by higher soil moisture variation under the altered precipitation frequency treatment, and were less impacted by the aforementioned stimulation in plant belowground biomass. The nematode community structure was not affected by the altered precipitation frequency treatment. This study provides experimental data for predicting responses of ecosystem functions to the projected changes in precipitation regimes. These findings are critical for making feasible decisions for the sustainable management of degraded grasslands.